Motivational Preferences of Employees in Requirements of Czech and Russian Transport and Logistics Enterprises - Lenka Ližbetinová; Miloš Hitka; Mikhail Kleymenov (Naše More (Dubrovnik), 2018)
The aim of the paper is to identify the employees' groups based on the differences in their motivation preferences in the environment of transport and logistics enterprises in selected regions. Loyal, satisfied and efficient employees are a key success factor for service enterprises in general. This is due to the fact that service sphere is characterized by the low level of anonymity of the service provider, therefore the level of professional approach of employees in direct interaction becomes the most important in terms of customer satisfaction. The paper represents partial result of research aimed at the identification of motivational preferences of employees in the specific conditions of logistics enterprises. The research was carried out in the Czech Republic and Russian Federation (Sverdlovsk region) in 2017 and the research sample consisted of 571 and 860 respondents employed in transport and logistics enterprises. There is a proposed use of Cluster analysis method in the paper. The research results obtained can help better understand the motivational preferences of the transport and logistics staff and thus create the possibility of more efficient formulation of incentive programs.